Strengthening the legislative function of the House of Regional Representatives In the Framework of bureaucratic reform in Indonesia - Agung, Wasana; Sarwono, Billy K (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The establishment of the House of Regional Representatives (DPD) aims to balance legislative power by implementing a two-room or bicameral system in representation. However, in reality, the authority of DPD in the field of legislation only acts as a co-legislator for the House of Representatives (DPR). The proposed law submitted by DPD is considered as DPR's initiative during the discussion, which indicates the need to strengthen the legislative function of DPD to be more equal to DPR. Methods: This research is conducted through juridical analysis of legislation and decisions of the Constitutional Court, particularly related to the legislative authority of DPD. This study also examines various legal documents and relevant literature to understand the dynamics and development of the legislative function of DPD in a bicameral representative system. Findings: The results showed that the decision of the Constitutional Court No. 92/PUU-X/2012 provides a bright spot for strengthening the legislative function of DPD, by giving the DPD the authority to propose draft laws as DPD initiatives and participate in the preparation of the National Legislation Programme. Nevertheless, DPD still requires further strengthening in the authority of the formation of laws that are general in nature as well as its involvement in the entire process of forming laws, from planning to discussion and approval. Conclusion: To strengthen the legislative function of DPD in the future, DPD needs to be given broader authority in the formation of laws and equal involvement in all stages of the legislative process with DPR. This is important to ensure balance in a bicameral system of representation and improve overall legislative effectiveness. Novelty/Originality of This Study: This study makes an original contribution by highlighting the need to strengthen the legislative role of DPD in Indonesia's bicameral system, as well as offering a new perspective on how the Constitutional Court decision can be a starting point for strengthening the legislative function of DPD. This analysis fills a gap in the literature on the role of DPD in legislation, especially in the context of strengthening the bicameral representative system in Indonesia.